2014
DOI: 10.1038/leu.2014.156
|View full text |Cite
|
Sign up to set email alerts
|

Sustained inhibition of STAT5, but not JAK2, is essential for TKI-induced cell death in chronic myeloid leukemia

Abstract: Kinase inhibitors block proliferative signals in BCR-ABL1+ leukemic cells, but their capacity to induce apoptosis is poorly understood. Initial studies suggested that very brief exposure to kinase inhibitors was sufficient to induce apoptosis in chronic myeloid leukemia (CML) cells. However, flaws in this experimental model have subsequently been identified, leading to the conclusion that apoptosis only occurs with sustained low-level kinase inhibition. Thus, the minimum duration of complete kinase inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…Therefore, the combination of TKI with multikinase inhibitors would be clinically relevant. Notably, the inhibition of phosphoStat5 (pStat5) constitutes a suitable target to abrogate CML cell growth and other types of leukemias, and, it is considered an attractive target to overcome resistance to clinically used Bcr-Abl kinase inhibitors [1214]. …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the combination of TKI with multikinase inhibitors would be clinically relevant. Notably, the inhibition of phosphoStat5 (pStat5) constitutes a suitable target to abrogate CML cell growth and other types of leukemias, and, it is considered an attractive target to overcome resistance to clinically used Bcr-Abl kinase inhibitors [1214]. …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, whilst JAK2 is upstream of STAT5, it was reported that deletion of JAK2 was not essential for myeloid (but was required for lymphoid) leukaemia in BCR-ABL1 mouse models [54]. It was proposed that BCR-ABL1 may directly activate STAT5 [54] and bypass endogenous regulation by JAK2 to promote leukaemogenesis [55,56]. Nevertheless, JAK inhibitors exhibit efficacy against primary CML cells, including TKI-resistant cells [57], and recent work suggests that JAK-signalling is important for stem cell biology (discussed later).…”
Section: Jak/statmentioning
confidence: 97%
“…IL-3 was described to induce STAT5 and Akt activation, both involved in leukemic cell survival. [33][34][35][36] NF-kB activation was reported to maintain BPDCN cell survival. 32 To investigate the effects of LXR activation on IL-3-induced STAT5 and Akt activation, CAL-1 cells were treated with increasing noncytotoxic concentrations of LXR agonists (1-10 mM, 24 hours), followed by IL-3 stimulation (10 ng/mL, 30 minutes).…”
Section: Lxr Activation Interferes With 2 Bpdcn Survival Pathways: Thmentioning
confidence: 99%